Życie gospodarczo-społeczne w klasztorach w Afryce Północnej w świetle wybranych pism św. Augustyna - Kołosowski, Tadeusz (Vox Patrum, 2019)
The article describes in the background the monastic activity of Augustine and in the light of his chosen writings the problem concerning of economic and social life in cloisters in Roman Africa. The author describes the part of Augustine in the development of the monachism in Northern Africa , the social structure of cloisters, the place and role of the work in the life of cenobites of clergymen and secular and matters of the property and the management with the monastic fortune.